(untitled) (SAINTEKBU, 2016)
The third generation wireless DS-CDMA networks are expected to support a wide variety of multimedia services such as high quality voice and data continuous (facsimile). The system quality of DS-CDMA is shown as bit error probability values or bit error rate (BER) both voice channel and continuous data channel. Bit error probability values are influenced by interference of the other users voice and data continuous (facsimile) . In the Final Project is made the genetic algorithm software for measuring the optimal system quality, specially for reverse channel. The optimal value result to explain the number active voice and data users that results minimum probability value on voice channel or data continuous (facsimile).